Biological properties of functional flavoring produced by enzymatic esterification of citronellol and geraniol present in Cymbopogon winterianus essential oil. Issue 24 (17th December 2021) - Staudt, Amanda; Duarte, Patrícia Fonseca; Amaral, Bruna Paes do; Peixoto Andrade, Bárbara Carolina de Oliveira; Simas, Naomi Kato; Correa Ramos Leal, Ivana; Sangenito, Leandro Stefano; Santos, André Luis Souza dos; de Oliveira, Débora; Junges, Alexander; Cansian, Rogério Luis; Paroul, Natalia
Abstract: The chemical composition and biological properties of citronella essential oil were modified by enzymatic esterification reaction of the major monoterpenic alcohols with cinnamic acid. The almost complete conversion of geraniol and citronellol present in the citronella ( Cymbopogon winterianus ) essential oil, into geranyl (99%) and citronellyl (98%) cinnamates was obtained after 48 hours of reaction using a molar ratio of 3:1 (cinnamic acid/alcohol), lipase concentration (Novozym 435) of 15% (w/w) and 70 °C. The esterified oil showed higher antimicrobial activity against Staphylococcus aureus bacteria resistant to oxacillin and penicillin and also greater larvicidal activity against Aedes aegypti larvae compared to unesterified oil. The results concerning the evaluation of toxicity against Artemia salina and cytotoxicity against monkey kidney epithelial cells also showed the superiority of the esterified oil. Graphical Abstract: UF0001